2009
DOI: 10.1056/nejmoa0900241
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Rosuvastatin in the Prevention of Venous Thromboembolism

Abstract: Background-Controversies persist on whether arterial and venous thrombosis share common pathways and whether treatments of known efficacy for one disease process have consistent benefits for the other. Observational studies have yielded variable estimates of the effect of statin therapy on risk of venous thromboembolism, and randomized evidence is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
384
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 659 publications
(400 citation statements)
references
References 41 publications
7
384
1
8
Order By: Relevance
“…Interestingly, lipid-lowering drugs seem to play a certain role in the development of VTE events, as the JUPITER trial showed a significant reduction in the occurrence of symptomatic VTE by the use of rosuvastatin compared to placebo in apparently healthy people [17]. Whether this effect is due to changes in lipid metabolism or to other mechanisms of action in hemostasis induced by statins remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lipid-lowering drugs seem to play a certain role in the development of VTE events, as the JUPITER trial showed a significant reduction in the occurrence of symptomatic VTE by the use of rosuvastatin compared to placebo in apparently healthy people [17]. Whether this effect is due to changes in lipid metabolism or to other mechanisms of action in hemostasis induced by statins remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1). Moreover, subclinical carotid atherosclerosis may also suggest a coexisting venous disorder among thalassemic patients because disease of either vascular bed is associated with contralateral cerebrovascular events and benefited by statin therapy [7,8,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Since the number of variables included in such analyses should be limited, we did not include established risk factors such as cancer, COPD, congestive heart failure, troponin or BNP in our analysis, since much larger studies have clearly demonstrated their impact on poor VTE outcome. In contrast to this, we decided to include established cardiovascular risk factors such as hyperlipidemia or diabetes in our risk factor assessment, since recent studies have indicated their impact on VTE [22][23][24]. Furthermore, given the demographic characteristics of our patients we suspected that the cardiovascular risk factors could have an impact on all-cause mortality.…”
Section: Outcome Event Rates and Risk Factorsmentioning
confidence: 99%